Monitoring of the National Oil and Wheat Flour Fortification Program in Cameroon Using a Program Impact Pathway Approach. Issue 8 (20th June 2019) - Mark, Henry E; Assiene, Jules G; Luo, Hanqi; Nankap, Martin; Ndjebayi, Alex; Ngnie-Teta, Ismael; Tarini, Ann; Pattar, Amrita; Killilea, David W; Brown, Kenneth H; Engle-Stone, Reina
ABSTRACT: Background: Since 2011 Cameroon has mandated the fortification of refined vegetable oil with vitamin A and wheat flour with iron, zinc, folic acid, and vitamin B-12. In 2012, measured fortification levels for flour, and particularly oil, were below target. Objectives: We assessed Cameroon's food fortification program using a program impact pathway (PIP) to identify barriers to optimal performance. Methods: We developed a PIP through literature review and key informant interviews. We conducted interviews at domestic factories for refined vegetable oil ( n = 9) and wheat flour ( n = 10). In 12 sentinel sites distributed nationally, we assessed availability and storage conditions of fortified foods in markets and frequency of consumption of fortified foods among women and children ( n = 613 households). Food samples were collected from factories, markets, and households for measurement of micronutrient content. Results: Two-thirds of factories presented quality certificates for recent premix purchases. All factories had in-house capacity for micronutrient analysis, but most used qualitative methods. Industries cited premix import taxes and access to external laboratories as constraints. Mean vitamin A levels were 141% (95% CI: 116%, 167%), 75% (95% CI: 62%, 89%), and 75% (95% CI: 60%, 90%) of target in individual samples from factories, markets, and households, respectively. Most industry flour samples appeared to be fortified, but micronutrient levels were low. Among composite flour samples from markets and households, the mean iron and zinc content was 25 mg/kg and 43 mg/kg, respectively, ∼45% of target levels; folic acid (36%) and vitamin B-12 (29%) levels were also low. In the previous week, the majority of respondents had consumed "fortifiable" oil (63% women and 52% children) and wheat flour (82% women and 86% children). Conclusions: In Cameroon, oil fortification program performance appears to have improved since 2012, but fortification levels remain below target, particularly for wheat flour. Consistent regulatory monitoring and program support, possibly through premix procurement and micronutrient analysis, are needed.